Maize biofortification using SSR markers for Zn, Fe and provitamin A - Rakesh K. Chahota; Satish K. Guleria; Pawan K. Sharma (Journal of BioScience and Biotechnology, 2024)
Maize, India's third most significant crop, employs directly more than 12 million growers and accounts for 2% of the country's overall agricultural crop production value. Scientists are continuously working to counter the hidden hunger i.e. the micronutrient malnutrition. Therefore, marker assisted breeding approach has been deployed to increase the micronutrients Zn, Fe and pro-vitamin A content in the maize lines HPK-2 and CM-40 at HAREC, Kullu Himachal Pradesh, India. DNA isolation was carried out with leaf samples of 172 inbred and two parental lines (HPK-2 and CM-40). HPK-2 and CM-40 were utilized to screen 227 SSR primers of maize on PAGE/agarose gel for polymorphism. The mapping population was genotyped using 160 polymorphic SSR primers, phenotyped for Zn, Fe levels in the grain kernel through Atomic Absorption Spectrophotometer. Kernel Fe and Zn content were 35–60 ppm and 5–20 ppm, respectively. One QTL for Fe was found on chromosome I, while three QTLs for Zn were found on chromosomes I and IX. Further, IARI, New Delhi and CSKHP Agricultural University, Palampur have collaborated on two provitamin A donors for β-carotene enhancement in maize. Crossing scheme was created by combining lines with higher Zn and Fe content (BAJIM 6-01, BAJIM 6-15, BAJIM 6-08, BAJIM 6-10, BAJIM 6-06) with lines with higher β-carotene content (CIMMYT-13, CIMMYT-4). Plants containing the crtRB1 allele were selected in the foreground selection using primers HYD65F, HYD66R, and HYD62R up to BC2F4 and F6 generation. The highest β-carotene content was found in crosses between Bajim-06-10*CIMMYT-13 and BC2F4 generation, with 12.54 ppm.